LA PERTINENCE DES INDUCTEURS UTILISES DANS L’ESTIMATION DU COUT DE PRODUCTION : CAS D’UN GROUPE DE SANDWICHERIES EN GARES FERROVIAIRES FRANÇAISES - Mohammed Mouadili; Youssef Elwazani (European Scientific Journal, ESJ, 2014)
Cost evaluation allows to company to make strategic decisions. So it is important that the method of allocating costs must be the closest to the real cost consumed, this method should be as relevant as possible to minimize errors in decision making. This article, based on case study, is trying to determine how the imprecision on evaluating costs influences trade policies and strategies of business development especially in the field of restoration. Thus, we also attempted to delineate the types of errors that affect the relevance of cost drivers. We finally concluded that the reliability and relevance of the information provided by evaluated costs, especially in a service activity, depends, not only on the correct choice of cost drivers, but also on integrating of company internal environment as critical variable in this relevance.